Calcitonin Gene-Related Peptide Monoclonal Antibodies Versus Botulinum Neurotoxin a in the Preventive Treatment of Chronic Migraine: An Adjusted Indirect Treatment Comparison Meta-Analysis - Chen, Yao-Yao; Ye, Xiao-Qian; Tang, Tai-Chun; She, Tian-Wei; Chen, Min; Zheng, Hui (Frontiers in Pharmacology, 2021)
Purpose: calcitonin gene-related peptide monoclonal antibodies (CGRPmAbs) are new agents approved by the US Food and Drug Administration for preventive treatment of chronic migraine. Direct comparison is lacking between CGRPmAbs and previously approved Botulinum neurotoxin A (BoNT-A). To perform adjusted indirect comparison between CGRPmAbs and BoNT-A through a meta-analysis. Methods: OVID MEDLINE, EMBASE and the Cochrane central register of controlled trials, clinical registries, and government websites were searched from inception to September 2019. Randomized controlled trials comparing CGRPmAbs or BoNT-A with placebo in the preventive treatment of chronic migraine were included. The primary outcomes were headache days and migraine days measured at week 12. Data were synthesized by using a frequentist approach; and the treatments were ranked by P-score. Results: We included 10 trials (n=4678) after screening 1049 candidates. Six trials were with low risk of bias. Fremanezumab had an effect similar to BoNT-A in the reduction of headache days at week 12 (standard mean difference [SMD] 0.08, 95%CI -0.55 to -0.7). Galcanezumab reduced more migraine days than BoNT-A at week 12 (SMD, -0.94, 95%CI -1.24 to -0.63); fremanezumab showed similar findings (SMD, -0.55, 95%CI -0.85 to -0.24). Galcanezumab and fremanezumab had better effect in mitigating headache impact at week 12. CGRPmAbs and BoNT-A had similar adverse event rate. Conclusions: CGRPmAbs and BoNT-A had similar effect in the preventive treatment of chronic migraine. BoNT-A might be preferentially selected owing to its cost-effectiveness profiles. Further studies with direct comparison of the two treatments are warranted.